(3GdhSGWI GdLfGFjI (B: s (3OQGSI ebGQfI (B/ s - (3EjeGf eUWai efUhQ eUWais; (3WGQb CMeO aJMj SQhQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JYQV GdQSGdI dCgejI GdhSGWI GdLfGFjI MjK JaJM GdHGH CeGe GdGSJYGfI HhSjW eaGhV(B: (3jbJQM GdMdhd h dG jaQVgG(B: (3jSYi Edi JYQja GdeJNGUejf Mbhbge h jOYe QZHJge aj GdhUhd Edi Md efUa(B: (3ceG EfgG JNJUQ GdELQGAGJ h Jbdd GdJcGdja h JMbb ef Ke SQYI GdMSe(B. (3ef gfG cGf GdGgJeGe HEaQGO OQGSI eSJbdI ddhSGWI GdLfGFjI JJHY GdOQGSGJ GdebGQfI h JSJgOa GdJYeb aj GdadSaI GdJj Jbhe YdjgG acQI GdYOGdI GdJaGhVjI(B: (3ceG GSJgOaJ GdOQGSI ageG CYeb dOhQ GdhSjW h JMOjOG COb ddWHjYI GdbGfhfjI dGJaGb GdhSGWI h eG jJQJH Ydj JhbjYg ef CKGQ ELQGFjI(B: (3h Pdc cdg MJi jecf JbOjQ fXGe GdhSGWI GdLfGFjI ef efXhQ GdCSS h GdefWdbGJ GdJj jbhe YdjgG GdfXGe GdbGfhfj GdeUQjs
(3jTJed Ydi edGMb(B: (3UaMGJ (B373-417s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2010s
(3HHdjhLQGajG(B: (3UaMGJ (B419-432s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdYOGdI GdJYGhfjIs; (3GdGbQGQ GdeSHb HGdPfHs; (3GdhSGWI GdLfGFjIs; (3HWA GdJbGVjs; (3Mb GdOhdI aj GdYbGHs; (3GdGeQ GdLfGFjs; (3GdJShjI GdLfGFjIs; (3GdUdM GdLfGFjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs